Development of Long-Circulating and Fusogenic Liposomes Co-encapsulating Paclitaxel and Doxorubicin in Synergistic Ratio for the Treatment of Breast Cancer - Roque, Marjorie C.; Franco, Marina Santiago; Vilela, José Mário Carneiro; Andrade, Margareth Spangler; de Barros, André Luís Branco; Leite, Elaine Amaral; Oliveira, Mônica Cristina (Current Drug Delivery, 2019)
Background: The co-encapsulation of paclitaxel (PTX) and doxorubicin (DXR) in liposomes has the potential to offer pharmacokinetic and pharmacodynamic advantages, providing delivery of both drugs to the tumor at the ratio required for synergism. Objective: To prepare and characterize long-circulating and fusogenic liposomes co-encapsulating PTX and DXR in the 1:10 molar ratio (LCFL-PTX/DXR). Methods: LCFL-PTX/DXR was prepared by the lipid film formation method. The release of PTX and DXR from liposomes was performed using a dialysis method. Studies of cytotoxicity, synergism, and cellular uptake were also carried out. Results: The encapsulation percentage of PTX and DXR was 74.1 ± 1.8 % and 89.6 ± 12.3%, respectively, and the mean diameter of the liposomes was 244.4 ± 28.1 nm. The vesicles remained stable for 30 days after their preparation. The drugs were simultaneously released from vesicles during 36 hours, maintaining the drugs combination in the previously established ratio. Cytotoxicity studies using 4T1 breast cancer cells showed lower inhibitory concentration 50% (IC50) value for LCFL-PTX/DXR treatment (0.27 ± 0.11 μm) compared to the values of free drugs treatment. In addition, the combination index (CI) assessed for treatment with LCFL-PTX/DXR was equal to 0.11 ± 0.04, showing strong synergism between the drugs. Cell uptake studies have confirmed that the molar ratio between PTX and DXR is maintained when the drugs are administered in liposomes. Conclusion: It was possible to obtain LCFL-PTX/DXR suitable for intravenous administration, capable of releasing the drugs in a fixed synergistic molar ratio in the tumor region.
Keywords: liposomes